Quantification of walking-based physical activity and sedentary time in individuals with Rett syndrome - Downs, Jennepher; Leonard, H.; Wong, K.; Newton, Nikki; Hill, Kylie (Wiley-Blackwell Publishing Ltd., 2017)
Aim: To quantify, in individuals with Rett syndrome with the capacity to walk, walking-based activity and sedentary time, and to analyse the influences of age, walking ability, scoliosis, and the severity of epilepsy. Method: Sixty-four participants with a mean age of 17 years and 7 months (standard deviation [SD] 9y) were recruited from the Australian Rett Syndrome Database for this cross-sectional study. Each participant wore a StepWatch Activity Monitor for at least 4 days. Linear regression models were used to assess relationships between daily step count and the proportion of waking hours spent in sedentary time with the covariates of age group, walking ability, presence of scoliosis, and frequency of seizures. Results: On average, 62% (SD 19%) of waking hours were sedentary and 20% (SD 8%) was at cadences lower than or equal to 20 steps in a minute. The median daily steps count was 5093 (interquartile range 2026-8602). Compared with females younger than 13 years of age and accounting for the effects of covariates, adults took fewer steps, and both adolescents and adults had more sedentary time. Interpretation: Adolescents and adults led the least active lives and would appear to be in particular need of interventions aiming to optimize slow walking-based physical activity and reduce sedentary time.